2023
DOI: 10.1002/jbt.23485
|View full text |Cite
|
Sign up to set email alerts
|

Influence of heavy metal exposure on gut microbiota: Recent advances

Ravidarshdeep Kaur,
Rakesh Rawal

Abstract: Gut microbiota plays a functionally important part in retaining the homeostasis of host physiology, however, under exposure of various heavy metals, the composition of gut biota is disturbed in relation to species diversity and richness. Ever since the increase of microbiome‐related studies during the last decade, many research studies have delivered an understanding of the reasons and concerns of gut microbiota‐related modifications. During the past decade, it's been confirmed from various studies that heavy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 52 publications
(70 reference statements)
0
2
0
Order By: Relevance
“…Literature evidence has indicated that metal ingestion can affect the gut microbiota ( 14 , 15 , 34 ). Therefore, we speculate that oral intake of Cu interacts with the gut microbiota, which in turn influences the host health.…”
Section: Discussionmentioning
confidence: 99%
“…Literature evidence has indicated that metal ingestion can affect the gut microbiota ( 14 , 15 , 34 ). Therefore, we speculate that oral intake of Cu interacts with the gut microbiota, which in turn influences the host health.…”
Section: Discussionmentioning
confidence: 99%
“…They have been connected to harmful outcomes such oxidative stress, carcinogenesis, DNA damage, and immune system weakening. Numerous recent research have suggested that exposure to heavy metals may be linked to gut microbial dysbiosis [ 9 ]. However, fewer studies have investigated the restoration of the diversified microbial community due to induced arsenic toxicity in mouse models.…”
Section: Introductionmentioning
confidence: 99%